A critical discourse analysis of risk communication on radio frequency exposure from telecommunication structures / Prasana Rosaline Fernandez - Prasana Rosaline , Fernandez (2016)
Radio frequency (RF) exposure from telecommunication structures in Malaysia is perceived by many to be a health hazard. This has led to contestation among the various stakeholders. Hence, this study examines thematically, how the social actors represent themselves and the other in the health debates on RF and, how social actions involving the exposure to RF are represented in the discourse by the various stakeholders. The research also explores ways to reduce the contestations of the various stakeholders by formulating recommendations for effective risk communication. This study plugs the gap in linguistic studies on risk as currently there is no analysis of risk on RF exposure from telecommunication structures from a Malaysian viewpoint and from a critical discourse analysis perspective. Risk has also not been researched through the lens of social actors and social actions as put forward by van Leeuwen (2008). Therefore, the premise of this research, which is a first-of-a-kind study in Malaysia, is to contribute to knowledge transfer in the telecommunication industry. The theoretical framework is based on Critical Discourse Analysis. The qualitative data comes from spoken conversations from thirty-one semi-structured interviews with representatives from seven stakeholder groups. The analytical frameworks for Research Questions 1 and 2 are based upon van Leeuwen’s (2008) Social Actor and Social Action Networks. Research Question 3 employs an adapted version of Key Steps in Applying Effective Risk Communication which was initiated by Kemp (2009) to draw on the key findings from Research Questions 1 and 2 to formulate the recommendations. In the representation of the social actors, the representation of ‘self’ is mostly positive and differ based on the different roles the stakeholders play but the ‘other’ are represented usually negatively. The social actors tend to align the ‘self’ with the in-group that supports their own representation while they distance themselves from ‘the other’ or the out-group who do not share the same beliefs and values. The self-representation is mostly congruent to the roles of the actor’s organization, their political affiliation and their position in society as the discourse carries differing ideologies and beliefs based on their respective roles. The representation validates that people tend to identify themselves with their own social groupings based on common knowledge, beliefs, ideologies, norms, and often place themselves in opposition to other social groupings that have differing views. The representations of social actions examine five themes: granting approval for the siting of telecommunication structures, construction of telecommunication structures, educating the public on RF, protests by residents, and media reporting on RF related issues. The social action representations’ generally corresponded with that of the self-representation of the social actors and it legitimises their role in the social practice. However, the reactions from the affected stakeholders’ delegitimise these representations as they feel that there are contradictions in the social actions and self-representation of the social actors. Overall, the representations impact trust which is vital in risk communication. Therefore, the recommendations stress on transparency and the participation of all stakeholders to facilitate the building, strengthening and repairing of trust.